Applied Control Theory for Embedded Systems. - Wescott, Tim. (Oxford : Elsevier Science & Technology, 2006)
A "crash course" on the basics of control theory in an embedded environment!.
front cover -- copyright -- table of contents -- front matter -- Preface -- What's on the CD-ROM? -- body -- 1 The Basics -- 1.1 Control Systems -- 1.2 Anatomy of a Control System -- 1.3 Closed Loop Control -- 1.4 Controllers -- 1.5 About This Book -- 2 Z Transforms -- 2.1 Signals and Systems -- 2.2 Difference Equations -- 2.3 The Z Transform -- 2.4 The Inverse Z Transform -- 2.5 Some Z Transform Properties -- 2.6 Transfer Functions -- 2.7 Stability in the Z Domain -- 2.8 Frequency Response -- 2.9 Conclusion -- 3 Performance -- 3.1 Tracking -- 3.2 Frequency Response -- 3.3 Disturbance Rejection -- 3.4 Conclusion -- 4 Block Diagrams -- 4.1 The Language of Blocks -- 4.2 Analyzing Systems with Block Diagrams -- 4.3 Conclusion -- 5 Analysis -- 5.1 Root Locus -- 5.2 Bode Plots -- 5.3 Nyquist Plots -- 5.4 Conclusion -- 6 Design -- 6.1 Controllers, Filters and Compensators -- 6.2 Compensation Topologies -- 6.3 Types of Compensators -- 6.4 Design Flow -- 6.5 Conclusion -- 7 Sampling Theory -- 7.1 Sampling -- 7.2 Aliasing -- 7.3 Reconstruction -- 7.4 Orthogonal Signals and Power -- 7.5 Random Noise -- 7.6 Nonideal Sampling -- 7.7 The Laplace Transform -- 7.8 z Domain Models -- 7.9 Conclusion -- 8 Nonlinear Systems -- 8.1 Characteristics of Nonlinear Systems -- 8.2 Some Nonlinearities -- 8.3 Linear Approximation -- 8.4 Nonlinear Compensators -- 8.5 Conclusion -- 9 Measuring Frequency Response -- 9.1 Overview -- 9.2 Measuring in Isolation -- 9.3 In-Loop Measurement -- 9.4 Real-World Issues -- 9.5 Software -- 9.6 Other Methods -- 10 Software Implications -- 10.1 Data Types -- 10.2 Quantization -- 10.3 Overflow -- 10.4 Resource Issues -- 10.5 Implementation Examples -- 10.6 Conclusion -- 11 Afterword -- 11.1 Tools -- 11.2 Bibliography -- back matter -- About the Author -- Index -- CD-ROM License Agreement.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Embedded computer systems -.; Electronic books